Burden of motorcyclists without helmets in a state without a universal helmet law: a propensity score analysis. Issue 1 (26th November 2020) - Jones, Michael D; Eastes, Joel G; Veljanoski, Damjan; Chapple, Kristina M; Bogert, James N; Weinberg, Jordan A
Abstract : Background: Although helmets are associated with reduction in mortality from motorcycle collisions, many states have failed to adopt universal helmet laws for motorcyclists, in part on the grounds that prior research is limited by study design (historical controls) and confounding variables. The goal of this study was to evaluate the association of helmet use in motorcycle collisions with hospital charges and mortality in trauma patients with propensity score analysis in a state without a universal helmet law. Methods: Motorcycle collision data from the Arizona State Trauma Registry from 2014 to 2017 were propensity score matched by regressing helmet use on patient age, sex, race/ethnicity, alcohol intoxication, illicit drug use, and comorbidities. Linear and logistic regression models were used to evaluate the impact of helmet use. Results: Our sample consisted of 6849 cases, of which 3699 (54.0%) were helmeted and 3150 (46.0%) without helmets. The cohort was 88.1% male with an average age of 40.9±16.0 years. Helmeted patients were less likely to be admitted to the intensive care unit (20.3% vs. 23.7%, OR 0.82 (0.72–0.93)) and ventilated (7.8% vs. 12.0%, OR 0.62 (0.52–0.75)). Propensity-matched analyses consisted of 2541 pairs and demonstrated helmet use to be associated with an 8% decrease in hospital charges ( B −0.075 (0.034)) and a 56% decrease in mortality (OR 0.44 (0.31–0.58)). Discussion: In a state without mandated helmet use for all motorcyclists, the burden of the unhelmeted rider is significant with respect to lives lost and healthcare charges incurred. Although the helmet law debate with respect to civil liberties is complex and unsettled, it appears clear that helmet use is strongly associated with both survival and less economic encumbrance on the state. Level of evidence: Level III, prognostic and epidemiological.